Klasifikasi Stunting Pada Anak Balita Sebagai Prediktor Kesehatan di Masa Dewasa - Maulindar, Joni; Jawahir Che Mustapha Yusuf; Juvinal Ximenes Guterres (LPPM POLITEKNIK LP3I BANDUNG, 2023)
This research aims to investigate the classification of stunting in toddlers as a predictor of health in adulthood. The research issue is related to the impact of stunting on child development, which can influence their health in adulthood. The research's objective is to construct a classification model that can identify stunting in toddlers based on a set of relevant variables. The research methodology involves secondary data analysis from surveys related to the health of toddlers and their adult data. The variables used in this research encompass weight, height, energy consumption, upper arm circumference, Body Mass Index (BMI), access to clean water, sanitation facilities, family medical history, parental education, socioeconomic status, age, gender, and geographical region. The research results demonstrate that the constructed classification model performs exceptionally well in identifying stunting in toddlers. The model achieves 100% accuracy, with high precision, recall, and F1-scores for both classes, i.e., class 0 (without stunting) and class 1 (with stunting). This signifies that the model possesses a strong capability to predict stunting in toddlers based on the utilized variables. Furthermore, specific variables such as weight, height, and BMI appear to have a significant influence on stunting classification. The research findings can serve as a foundation for developing more effective intervention programs to prevent stunting in toddlers. Thus, this research makes a significant contribution to efforts to enhance the health of toddlers and prevent health issues in adulthood resulting from stunting.